PENGARUH KUALITAS LAYANAN, CITRA MEREK, KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PELEMBAB WAJAH MEREK SARIAYU DIKOTA BATAM - Magdalena Leony Fabila Daeli; Inda Sukati Sukati (LPPM Universitas Putera Batam, 2026)
This study aims to determine how service quality, brand image, and product quality influence customers' decisions to purchase Sariayu facial moisturisers in the city of Batam. The individuals involved in this study are purchasers of Sariayu facial moisturisers. The purposive sampling method uses questionnaires to collect responses. The population of this study is very large and unlimited. As a result, the sample to be studied consists of 204 respondents. This study analyses primary data; multiple linear regression analysis is used as the analysis tool. The purpose of this study is to determine how independent variables influence dependent variables. The results of the multiple linear regression test show that service quality, brand image, and product quality have a significant impact on consumer decisions when deciding to purchase Sariayu facial moisturisers in Batam City. From the results of this study, it can be concluded that superior service quality, brand image, and product quality will increase consumers' decisions to purchase these products.